Incorporating Social Justice into Statistical Instruction: Using Action Research to Impact Pre-Service Teachers - Conway, Basil M; Nguyen, Ha (International journal for the scholarship of teaching and learning, 2020)
The following action research depicts how two researchers from two universities merged their courses and goals of instruction to impact change in future teachers. Two currently practicing middle school teachers from one university worked with researchers to develop a social justice lesson that had relevance to seventeen K-8 pre-service teachers at another university to promote changes in beliefs about equitable teaching practices and policy. Findings from pre- and post-surveys, field notes during enactment, and reflections teachers found teaching statistics for social justice (TS4SJ) in this setting provided an increased responsiveness to the needs of students and statistical connections while also attending to excuses by those facing dilemmas in belief and racial dominance.